Are environmental responsibility companies socially responsible? Evidence from tax planning activities - Mohd Waliuddin, Mohd Razali; Evan, Lau; Damien Lee, Lung Yau; Rossazana, Ab. Rahim (AESS Publications, 2024)
Malaysia's Income Tax Act of 1967 does not impose penalties on environmentally friendly companies engaged in tax planning. The primary objective of this study is to examine the relationship between a company's environmental activities and the tax planning of publicly listed companies in Malaysia. A sample of 158 publicly listed companies from various industries except for financial institutions in Bursa Malaysia will be used. The annual report included non-financial data such as the environmental responsibility variable. The annual report was also used to collect the remaining data including tax planning, profitability, size and debt ratio. The multiple regression analysis indicates that companies actively participating in environmental initiatives are more inclined to adopt socially responsible tax practices to uphold their credibility among stakeholders. These companies reinforce their reputation as responsible corporate citizens committed to sustainability by demonstrating consistency between their environmental and tax practices. This study additionally revealed a positive relationship between larger companies and tax planning due to their greater access to resources and experience which enabled them to employ more advanced tax planning tactics. The utilization of permanent and temporary book tax differences (BTDs) as factors for tax planning presents a more sophisticated approach to evaluating corporate tax strategies as suggested by future research.